Theory Transfer

(*  Title:      HOL/Transfer.thy
    Author:     Brian Huffman, TU Muenchen
    Author:     Ondrej Kuncar, TU Muenchen
*)

section Generic theorem transfer using relations

theory Transfer
imports Basic_BNF_LFPs Hilbert_Choice Metis
begin

subsection Relator for function space

bundle lifting_syntax
begin
  notation rel_fun  (infixr "===>" 55)
  notation map_fun  (infixr "--->" 55)
end

context includes lifting_syntax
begin

lemma rel_funD2:
  assumes "rel_fun A B f g" and "A x x"
  shows "B (f x) (g x)"
  using assms by (rule rel_funD)

lemma rel_funE:
  assumes "rel_fun A B f g" and "A x y"
  obtains "B (f x) (g y)"
  using assms by (simp add: rel_fun_def)

lemmas rel_fun_eq = fun.rel_eq

lemma rel_fun_eq_rel:
shows "rel_fun (=) R = (λf g. x. R (f x) (g x))"
  by (simp add: rel_fun_def)


subsection Transfer method

text Explicit tag for relation membership allows for
  backward proof methods.

definition Rel :: "('a  'b  bool)  'a  'b  bool"
  where "Rel r  r"

text Handling of equality relations

definition is_equality :: "('a  'a  bool)  bool"
  where "is_equality R  R = (=)"

lemma is_equality_eq: "is_equality (=)"
  unfolding is_equality_def by simp

text Reverse implication for monotonicity rules

definition rev_implies where
  "rev_implies x y  (y  x)"

text Handling of meta-logic connectives

definition transfer_forall where
  "transfer_forall  All"

definition transfer_implies where
  "transfer_implies  (⟶)"

definition transfer_bforall :: "('a  bool)  ('a  bool)  bool"
  where "transfer_bforall  (λP Q. x. P x  Q x)"

lemma transfer_forall_eq: "(x. P x)  Trueprop (transfer_forall (λx. P x))"
  unfolding atomize_all transfer_forall_def ..

lemma transfer_implies_eq: "(A  B)  Trueprop (transfer_implies A B)"
  unfolding atomize_imp transfer_implies_def ..

lemma transfer_bforall_unfold:
  "Trueprop (transfer_bforall P (λx. Q x))  (x. P x  Q x)"
  unfolding transfer_bforall_def atomize_imp atomize_all ..

lemma transfer_start: "P; Rel (=) P Q  Q"
  unfolding Rel_def by simp

lemma transfer_start': "P; Rel (⟶) P Q  Q"
  unfolding Rel_def by simp

lemma transfer_prover_start: "x = x'; Rel R x' y  Rel R x y"
  by simp

lemma untransfer_start: "Q; Rel (=) P Q  P"
  unfolding Rel_def by simp

lemma Rel_eq_refl: "Rel (=) x x"
  unfolding Rel_def ..

lemma Rel_app:
  assumes "Rel (A ===> B) f g" and "Rel A x y"
  shows "Rel B (f x) (g y)"
  using assms unfolding Rel_def rel_fun_def by fast

lemma Rel_abs:
  assumes "x y. Rel A x y  Rel B (f x) (g y)"
  shows "Rel (A ===> B) (λx. f x) (λy. g y)"
  using assms unfolding Rel_def rel_fun_def by fast

subsection Predicates on relations, i.e. ``class constraints''

definition left_total :: "('a  'b  bool)  bool"
  where "left_total R  (x. y. R x y)"

definition left_unique :: "('a  'b  bool)  bool"
  where "left_unique R  (x y z. R x z  R y z  x = y)"

definition right_total :: "('a  'b  bool)  bool"
  where "right_total R  (y. x. R x y)"

definition right_unique :: "('a  'b  bool)  bool"
  where "right_unique R  (x y z. R x y  R x z  y = z)"

definition bi_total :: "('a  'b  bool)  bool"
  where "bi_total R  (x. y. R x y)  (y. x. R x y)"

definition bi_unique :: "('a  'b  bool)  bool"
  where "bi_unique R 
    (x y z. R x y  R x z  y = z) 
    (x y z. R x z  R y z  x = y)"

lemma left_unique_iff: "left_unique R  (z. 1x. R x z)"
  unfolding Uniq_def left_unique_def by force

lemma left_uniqueI: "(x y z.  A x z; A y z   x = y)  left_unique A"
unfolding left_unique_def by blast

lemma left_uniqueD: " left_unique A; A x z; A y z   x = y"
unfolding left_unique_def by blast

lemma left_totalI:
  "(x. y. R x y)  left_total R"
unfolding left_total_def by blast

lemma left_totalE:
  assumes "left_total R"
  obtains "(x. y. R x y)"
using assms unfolding left_total_def by blast

lemma bi_uniqueDr: " bi_unique A; A x y; A x z   y = z"
  by(simp add: bi_unique_def)

lemma bi_uniqueDl: " bi_unique A; A x y; A z y   x = z"
  by(simp add: bi_unique_def)

lemma bi_unique_iff: "bi_unique R  (z. 1x. R x z)  (z. 1x. R z x)"
  unfolding Uniq_def bi_unique_def by force

lemma right_unique_iff: "right_unique R  (z. 1x. R z x)"
  unfolding Uniq_def right_unique_def by force

lemma right_uniqueI: "(x y z.  A x y; A x z   y = z)  right_unique A"
unfolding right_unique_def by fast

lemma right_uniqueD: " right_unique A; A x y; A x z   y = z"
unfolding right_unique_def by fast

lemma right_totalI: "(y. x. A x y)  right_total A"
by(simp add: right_total_def)

lemma right_totalE:
  assumes "right_total A"
  obtains x where "A x y"
using assms by(auto simp add: right_total_def)

lemma right_total_alt_def2:
  "right_total R  ((R ===> (⟶)) ===> (⟶)) All All" (is "?lhs = ?rhs")
proof
  assume ?lhs then show ?rhs
    unfolding right_total_def rel_fun_def by blast
next
  assume §: ?rhs
  show ?lhs
    using § [unfolded rel_fun_def, rule_format, of "λx. True" "λy. x. R x y"]
    unfolding right_total_def by blast
qed

lemma right_unique_alt_def2:
  "right_unique R  (R ===> R ===> (⟶)) (=) (=)"
  unfolding right_unique_def rel_fun_def by auto

lemma bi_total_alt_def2:
  "bi_total R  ((R ===> (=)) ===> (=)) All All" (is "?lhs = ?rhs")
proof
  assume ?lhs then show ?rhs
    unfolding bi_total_def rel_fun_def by blast
next
  assume §: ?rhs
  show ?lhs
    using § [unfolded rel_fun_def, rule_format, of "λx. y. R x y" "λy. True"]
    using § [unfolded rel_fun_def, rule_format, of "λx. True" "λy. x. R x y"]
    by (auto simp: bi_total_def)
qed

lemma bi_unique_alt_def2:
  "bi_unique R  (R ===> R ===> (=)) (=) (=)"
  unfolding bi_unique_def rel_fun_def by auto

lemma [simp]:
  shows left_unique_conversep: "left_unique A¯¯  right_unique A"
    and right_unique_conversep: "right_unique A¯¯  left_unique A"
  by(auto simp add: left_unique_def right_unique_def)

lemma [simp]:
  shows left_total_conversep: "left_total A¯¯  right_total A"
    and right_total_conversep: "right_total A¯¯  left_total A"
  by(simp_all add: left_total_def right_total_def)

lemma bi_unique_conversep [simp]: "bi_unique R¯¯ = bi_unique R"
  by(auto simp add: bi_unique_def)

lemma bi_total_conversep [simp]: "bi_total R¯¯ = bi_total R"
  by(auto simp add: bi_total_def)

lemma right_unique_alt_def: "right_unique R = (conversep R OO R  (=))" unfolding right_unique_def by blast
lemma left_unique_alt_def: "left_unique R = (R OO (conversep R)  (=))" unfolding left_unique_def by blast

lemma right_total_alt_def: "right_total R = (conversep R OO R  (=))" unfolding right_total_def by blast
lemma left_total_alt_def: "left_total R = (R OO conversep R  (=))" unfolding left_total_def by blast

lemma bi_total_alt_def: "bi_total A = (left_total A  right_total A)"
unfolding left_total_def right_total_def bi_total_def by blast

lemma bi_unique_alt_def: "bi_unique A = (left_unique A  right_unique A)"
unfolding left_unique_def right_unique_def bi_unique_def by blast

lemma bi_totalI: "left_total R  right_total R  bi_total R"
unfolding bi_total_alt_def ..

lemma bi_uniqueI: "left_unique R  right_unique R  bi_unique R"
unfolding bi_unique_alt_def ..

end


lemma is_equality_lemma: "(R. is_equality R  PROP (P R))  PROP (P (=))"
  unfolding is_equality_def
proof (rule equal_intr_rule)
  show "(R. R = (=)  PROP P R)  PROP P (=)"
    apply (drule meta_spec)
    apply (erule meta_mp [OF _ refl])
    done
qed simp

lemma Domainp_lemma: "(R. Domainp T = R  PROP (P R))  PROP (P (Domainp T))"
proof (rule equal_intr_rule)
  show "(R. Domainp T = R  PROP P R)  PROP P (Domainp T)"
    apply (drule meta_spec)
    apply (erule meta_mp [OF _ refl])
    done
qed simp

ML_file Tools/Transfer/transfer.ML
declare refl [transfer_rule]

hide_const (open) Rel

context includes lifting_syntax
begin

text Handling of domains

lemma Domainp_iff: "Domainp T x  (y. T x y)"
  by auto

lemma Domainp_refl[transfer_domain_rule]:
  "Domainp T = Domainp T" ..

lemma Domain_eq_top[transfer_domain_rule]: "Domainp (=) = top" by auto

lemma Domainp_pred_fun_eq[relator_domain]:
  assumes "left_unique T"
  shows "Domainp (T ===> S) = pred_fun (Domainp T) (Domainp S)"   (is "?lhs = ?rhs")
proof (intro ext iffI)
  fix x
  assume "?lhs x"
  then show "?rhs x"
    using assms unfolding rel_fun_def pred_fun_def by blast
next
  fix x
  assume "?rhs x"
  then have "g. y xa. T xa y  S (x xa) (g y)"
    using assms unfolding Domainp_iff left_unique_def  pred_fun_def
    by (intro choice) blast
  then show "?lhs x"
    by blast
qed

text Properties are preserved by relation composition.

lemma OO_def: "R OO S = (λx z. y. R x y  S y z)"
  by auto

lemma bi_total_OO: "bi_total A; bi_total B  bi_total (A OO B)"
  unfolding bi_total_def OO_def by fast

lemma bi_unique_OO: "bi_unique A; bi_unique B  bi_unique (A OO B)"
  unfolding bi_unique_def OO_def by blast

lemma right_total_OO:
  "right_total A; right_total B  right_total (A OO B)"
  unfolding right_total_def OO_def by fast

lemma right_unique_OO:
  "right_unique A; right_unique B  right_unique (A OO B)"
  unfolding right_unique_def OO_def by fast

lemma left_total_OO: "left_total R  left_total S  left_total (R OO S)"
  unfolding left_total_def OO_def by fast

lemma left_unique_OO: "left_unique R  left_unique S  left_unique (R OO S)"
  unfolding left_unique_def OO_def by blast


subsection Properties of relators

lemma left_total_eq[transfer_rule]: "left_total (=)"
  unfolding left_total_def by blast

lemma left_unique_eq[transfer_rule]: "left_unique (=)"
  unfolding left_unique_def by blast

lemma right_total_eq [transfer_rule]: "right_total (=)"
  unfolding right_total_def by simp

lemma right_unique_eq [transfer_rule]: "right_unique (=)"
  unfolding right_unique_def by simp

lemma bi_total_eq[transfer_rule]: "bi_total (=)"
  unfolding bi_total_def by simp

lemma bi_unique_eq[transfer_rule]: "bi_unique (=)"
  unfolding bi_unique_def by simp

lemma left_total_fun[transfer_rule]:
  assumes "left_unique A" "left_total B"
  shows "left_total (A ===> B)"
  unfolding left_total_def 
proof
  fix f
  show "Ex ((A ===> B) f)"
    unfolding rel_fun_def
  proof (intro exI strip)
    fix x y
    assume A: "A x y"
    have "(THE x. A x y) = x"
      using A assms by (simp add: left_unique_def the_equality)
    then show "B (f x) (SOME z. B (f (THE x. A x y)) z)"
      using assms by (force simp: left_total_def intro: someI_ex)
  qed
qed

lemma left_unique_fun[transfer_rule]:
  "left_total A; left_unique B  left_unique (A ===> B)"
  unfolding left_total_def left_unique_def rel_fun_def
  by (clarify, rule ext, fast)

lemma right_total_fun [transfer_rule]:
  assumes "right_unique A" "right_total B"
  shows "right_total (A ===> B)"
  unfolding right_total_def 
proof
  fix g
  show "x. (A ===> B) x g"
    unfolding rel_fun_def
  proof (intro exI strip)
    fix x y
    assume A: "A x y"
    have "(THE y. A x y) = y"
      using A assms by (simp add: right_unique_def the_equality)
    then show "B (SOME z. B z (g (THE y. A x y))) (g y)"
      using assms by (force simp: right_total_def intro: someI_ex)
  qed
qed

lemma right_unique_fun [transfer_rule]:
  "right_total A; right_unique B  right_unique (A ===> B)"
  unfolding right_total_def right_unique_def rel_fun_def
  by (clarify, rule ext, fast)

lemma bi_total_fun[transfer_rule]:
  "bi_unique A; bi_total B  bi_total (A ===> B)"
  unfolding bi_unique_alt_def bi_total_alt_def
  by (blast intro: right_total_fun left_total_fun)

lemma bi_unique_fun[transfer_rule]:
  "bi_total A; bi_unique B  bi_unique (A ===> B)"
  unfolding bi_unique_alt_def bi_total_alt_def
  by (blast intro: right_unique_fun left_unique_fun)

end

lemma if_conn:
  "(if P  Q then t else e) = (if P then if Q then t else e else e)"
  "(if P  Q then t else e) = (if P then t else if Q then t else e)"
  "(if P  Q then t else e) = (if P then if Q then t else e else t)"
  "(if ¬ P then t else e) = (if P then e else t)"
by auto

ML_file Tools/Transfer/transfer_bnf.ML
ML_file Tools/BNF/bnf_fp_rec_sugar_transfer.ML

declare pred_fun_def [simp]
declare rel_fun_eq [relator_eq]

(* Delete the automated generated rule from the bnf command;
  we have a more general rule (Domainp_pred_fun_eq) that subsumes it. *)
declare fun.Domainp_rel[relator_domain del]

subsection Transfer rules

context includes lifting_syntax
begin

lemma Domainp_forall_transfer [transfer_rule]:
  assumes "right_total A"
  shows "((A ===> (=)) ===> (=))
    (transfer_bforall (Domainp A)) transfer_forall"
  using assms unfolding right_total_def
  unfolding transfer_forall_def transfer_bforall_def rel_fun_def Domainp_iff
  by fast

text Transfer rules using implication instead of equality on booleans.

lemma transfer_forall_transfer [transfer_rule]:
  "bi_total A  ((A ===> (=)) ===> (=)) transfer_forall transfer_forall"
  "right_total A  ((A ===> (=)) ===> implies) transfer_forall transfer_forall"
  "right_total A  ((A ===> implies) ===> implies) transfer_forall transfer_forall"
  "bi_total A  ((A ===> (=)) ===> rev_implies) transfer_forall transfer_forall"
  "bi_total A  ((A ===> rev_implies) ===> rev_implies) transfer_forall transfer_forall"
  unfolding transfer_forall_def rev_implies_def rel_fun_def right_total_def bi_total_def
  by fast+

lemma transfer_implies_transfer [transfer_rule]:
  "((=)        ===> (=)        ===> (=)       ) transfer_implies transfer_implies"
  "(rev_implies ===> implies     ===> implies    ) transfer_implies transfer_implies"
  "(rev_implies ===> (=)        ===> implies    ) transfer_implies transfer_implies"
  "((=)        ===> implies     ===> implies    ) transfer_implies transfer_implies"
  "((=)        ===> (=)        ===> implies    ) transfer_implies transfer_implies"
  "(implies     ===> rev_implies ===> rev_implies) transfer_implies transfer_implies"
  "(implies     ===> (=)        ===> rev_implies) transfer_implies transfer_implies"
  "((=)        ===> rev_implies ===> rev_implies) transfer_implies transfer_implies"
  "((=)        ===> (=)        ===> rev_implies) transfer_implies transfer_implies"
  unfolding transfer_implies_def rev_implies_def rel_fun_def by auto

lemma eq_imp_transfer [transfer_rule]:
  "right_unique A  (A ===> A ===> (⟶)) (=) (=)"
  unfolding right_unique_alt_def2 .

text Transfer rules using equality.

lemma left_unique_transfer [transfer_rule]:
  assumes "right_total A"
  assumes "right_total B"
  assumes "bi_unique A"
  shows "((A ===> B ===> (=)) ===> implies) left_unique left_unique"
  using assms unfolding left_unique_def right_total_def bi_unique_def rel_fun_def
  by metis

lemma eq_transfer [transfer_rule]:
  assumes "bi_unique A"
  shows "(A ===> A ===> (=)) (=) (=)"
  using assms unfolding bi_unique_def rel_fun_def by auto

lemma right_total_Ex_transfer[transfer_rule]:
  assumes "right_total A"
  shows "((A ===> (=)) ===> (=)) (Bex (Collect (Domainp A))) Ex"
  using assms unfolding right_total_def Bex_def rel_fun_def Domainp_iff
  by fast

lemma right_total_All_transfer[transfer_rule]:
  assumes "right_total A"
  shows "((A ===> (=)) ===> (=)) (Ball (Collect (Domainp A))) All"
  using assms unfolding right_total_def Ball_def rel_fun_def Domainp_iff
  by fast

context
  includes lifting_syntax
begin

lemma right_total_fun_eq_transfer:
  assumes [transfer_rule]: "right_total A" "bi_unique B"
  shows "((A ===> B) ===> (A ===> B) ===> (=)) (λf g. xCollect(Domainp A). f x = g x) (=)"
  unfolding fun_eq_iff
  by transfer_prover

end

lemma All_transfer [transfer_rule]:
  assumes "bi_total A"
  shows "((A ===> (=)) ===> (=)) All All"
  using assms unfolding bi_total_def rel_fun_def by fast

lemma Ex_transfer [transfer_rule]:
  assumes "bi_total A"
  shows "((A ===> (=)) ===> (=)) Ex Ex"
  using assms unfolding bi_total_def rel_fun_def by fast

lemma Ex1_parametric [transfer_rule]:
  assumes [transfer_rule]: "bi_unique A" "bi_total A"
  shows "((A ===> (=)) ===> (=)) Ex1 Ex1"
unfolding Ex1_def by transfer_prover

declare If_transfer [transfer_rule]

lemma Let_transfer [transfer_rule]: "(A ===> (A ===> B) ===> B) Let Let"
  unfolding rel_fun_def by simp

declare id_transfer [transfer_rule]

declare comp_transfer [transfer_rule]

lemma curry_transfer [transfer_rule]:
  "((rel_prod A B ===> C) ===> A ===> B ===> C) curry curry"
  unfolding curry_def by transfer_prover

lemma fun_upd_transfer [transfer_rule]:
  assumes [transfer_rule]: "bi_unique A"
  shows "((A ===> B) ===> A ===> B ===> A ===> B) fun_upd fun_upd"
  unfolding fun_upd_def  by transfer_prover

lemma case_nat_transfer [transfer_rule]:
  "(A ===> ((=) ===> A) ===> (=) ===> A) case_nat case_nat"
  unfolding rel_fun_def by (simp split: nat.split)

lemma rec_nat_transfer [transfer_rule]:
  "(A ===> ((=) ===> A ===> A) ===> (=) ===> A) rec_nat rec_nat"
  unfolding rel_fun_def
  apply safe
  subgoal for _ _ _ _ _ n
    by (induction n) simp_all
  done


lemma funpow_transfer [transfer_rule]:
  "((=) ===> (A ===> A) ===> (A ===> A)) compow compow"
  unfolding funpow_def by transfer_prover

lemma mono_transfer[transfer_rule]:
  assumes [transfer_rule]: "bi_total A"
  assumes [transfer_rule]: "(A ===> A ===> (=)) (≤) (≤)"
  assumes [transfer_rule]: "(B ===> B ===> (=)) (≤) (≤)"
  shows "((A ===> B) ===> (=)) mono mono"
unfolding mono_def by transfer_prover

lemma right_total_relcompp_transfer[transfer_rule]:
  assumes [transfer_rule]: "right_total B"
  shows "((A ===> B ===> (=)) ===> (B ===> C ===> (=)) ===> A ===> C ===> (=))
    (λR S x z. yCollect (Domainp B). R x y  S y z) (OO)"
unfolding OO_def by transfer_prover

lemma relcompp_transfer[transfer_rule]:
  assumes [transfer_rule]: "bi_total B"
  shows "((A ===> B ===> (=)) ===> (B ===> C ===> (=)) ===> A ===> C ===> (=)) (OO) (OO)"
unfolding OO_def by transfer_prover

lemma right_total_Domainp_transfer[transfer_rule]:
  assumes [transfer_rule]: "right_total B"
  shows "((A ===> B ===> (=)) ===> A ===> (=)) (λT x. yCollect(Domainp B). T x y) Domainp"
apply(subst(2) Domainp_iff[abs_def]) by transfer_prover

lemma Domainp_transfer[transfer_rule]:
  assumes [transfer_rule]: "bi_total B"
  shows "((A ===> B ===> (=)) ===> A ===> (=)) Domainp Domainp"
unfolding Domainp_iff by transfer_prover

lemma reflp_transfer[transfer_rule]:
  "bi_total A  ((A ===> A ===> (=)) ===> (=)) reflp reflp"
  "right_total A  ((A ===> A ===> implies) ===> implies) reflp reflp"
  "right_total A  ((A ===> A ===> (=)) ===> implies) reflp reflp"
  "bi_total A  ((A ===> A ===> rev_implies) ===> rev_implies) reflp reflp"
  "bi_total A  ((A ===> A ===> (=)) ===> rev_implies) reflp reflp"
unfolding reflp_def rev_implies_def bi_total_def right_total_def rel_fun_def
by fast+

lemma right_unique_transfer [transfer_rule]:
  " right_total A; right_total B; bi_unique B 
   ((A ===> B ===> (=)) ===> implies) right_unique right_unique"
unfolding right_unique_def right_total_def bi_unique_def rel_fun_def
by metis

lemma left_total_parametric [transfer_rule]:
  assumes [transfer_rule]: "bi_total A" "bi_total B"
  shows "((A ===> B ===> (=)) ===> (=)) left_total left_total"
unfolding left_total_def by transfer_prover

lemma right_total_parametric [transfer_rule]:
  assumes [transfer_rule]: "bi_total A" "bi_total B"
  shows "((A ===> B ===> (=)) ===> (=)) right_total right_total"
unfolding right_total_def by transfer_prover

lemma left_unique_parametric [transfer_rule]:
  assumes [transfer_rule]: "bi_unique A" "bi_total A" "bi_total B"
  shows "((A ===> B ===> (=)) ===> (=)) left_unique left_unique"
unfolding left_unique_def by transfer_prover

lemma prod_pred_parametric [transfer_rule]:
  "((A ===> (=)) ===> (B ===> (=)) ===> rel_prod A B ===> (=)) pred_prod pred_prod"
unfolding prod.pred_set Basic_BNFs.fsts_def Basic_BNFs.snds_def fstsp.simps sndsp.simps 
by simp transfer_prover

lemma apfst_parametric [transfer_rule]:
  "((A ===> B) ===> rel_prod A C ===> rel_prod B C) apfst apfst"
unfolding apfst_def by transfer_prover

lemma rel_fun_eq_eq_onp: "((=) ===> eq_onp P) = eq_onp (λf. x. P(f x))"
unfolding eq_onp_def rel_fun_def by auto

lemma rel_fun_eq_onp_rel:
  shows "((eq_onp R) ===> S) = (λf g. x. R x  S (f x) (g x))"
by (auto simp add: eq_onp_def rel_fun_def)

lemma eq_onp_transfer [transfer_rule]:
  assumes [transfer_rule]: "bi_unique A"
  shows "((A ===> (=)) ===> A ===> A ===> (=)) eq_onp eq_onp"
unfolding eq_onp_def by transfer_prover

lemma rtranclp_parametric [transfer_rule]:
  assumes "bi_unique A" "bi_total A"
  shows "((A ===> A ===> (=)) ===> A ===> A ===> (=)) rtranclp rtranclp"
proof(rule rel_funI iffI)+
  fix R :: "'a  'a  bool" and R' x y x' y'
  assume R: "(A ===> A ===> (=)) R R'" and "A x x'"
  {
    assume "R** x y" "A y y'"
    thus "R'** x' y'"
    proof(induction arbitrary: y')
      case base
      with bi_unique A A x x' have "x' = y'" by(rule bi_uniqueDr)
      thus ?case by simp
    next
      case (step y z z')
      from bi_total A obtain y' where "A y y'" unfolding bi_total_def by blast
      hence "R'** x' y'" by(rule step.IH)
      moreover from R A y y' A z z' R y z
      have "R' y' z'" by(auto dest: rel_funD)
      ultimately show ?case ..
    qed
  next
    assume "R'** x' y'" "A y y'"
    thus "R** x y"
    proof(induction arbitrary: y)
      case base
      with bi_unique A A x x' have "x = y" by(rule bi_uniqueDl)
      thus ?case by simp
    next
      case (step y' z' z)
      from bi_total A obtain y where "A y y'" unfolding bi_total_def by blast
      hence "R** x y" by(rule step.IH)
      moreover from R A y y' A z z' R' y' z'
      have "R y z" by(auto dest: rel_funD)
      ultimately show ?case ..
    qed
  }
qed

lemma right_unique_parametric [transfer_rule]:
  assumes [transfer_rule]: "bi_total A" "bi_unique B" "bi_total B"
  shows "((A ===> B ===> (=)) ===> (=)) right_unique right_unique"
  unfolding right_unique_def by transfer_prover

lemma map_fun_parametric [transfer_rule]:
  "((A ===> B) ===> (C ===> D) ===> (B ===> C) ===> A ===> D) map_fun map_fun"
  unfolding map_fun_def by transfer_prover

end


subsection constof_bool and constof_nat

context
  includes lifting_syntax
begin

lemma transfer_rule_of_bool:
  ((⟷) ===> (≅)) of_bool of_bool
    if [transfer_rule]: 0  0 1  1
    for R :: 'a::zero_neq_one  'b::zero_neq_one  bool  (infix  50)
  unfolding of_bool_def by transfer_prover

lemma transfer_rule_of_nat:
  "((=) ===> (≅)) of_nat of_nat"
    if [transfer_rule]: 0  0 1  1
    ((≅) ===> (≅) ===> (≅)) (+) (+)
  for R :: 'a::semiring_1  'b::semiring_1  bool  (infix  50)
  unfolding of_nat_def by transfer_prover

end

end